Banning super short-haul flights: Environmental evidence or political turbulence?. (October 2022) - Dobruszkes, Frédéric; Mattioli, Giulio; Mathieu, Laurette
Abstract: Several countries have considered banning or even decided to ban or tax super short-haul flights, arguing that the availability of rail alternatives makes them unnecessary. Such policies result from the need for governments to be seen as acting to mitigate climate change and scholars favouring energy (climate) efficiency perspectives over the absolute amount of fuel burnt (greenhouse gas emissions emitted). Yet climate change is due to absolute emissions, and it is a fact that the longer a flight is, the greater the amount of fuel is burnt (emissions). Considering all departing flights from 31 European countries, our study found that flights shorter than 500 km account for 27.9% of departures but 5.9% of fuel burnt. In contrast, flights longer than 4, 000 km account for 6.2% of departures but 47.0% of fuel burnt, although with significant variation across countries. We conclude that targeting shorter flights (which often exist to alleviate physical obstacles imposed by physical geography) will contribute little to reducing the impact of aviation on climate, and that policy initiatives that target longer flights are urgently needed. Highlights: This paper assesses the rationale for banning super short-haul passenger flights. All commercial passenger flights from 31 European countries have been considered. Flights shorter than 500 km account for 5.9% of aviation fuel burnt. Flights longer than 4000 km account for 47.0% of aviation fuel burnt. Reducing the impact of aviation on climate requires the targeting of longer flights.